Синестеземи в українському медійному тексті мистецької тематики: неспеціалізовані інтернет-видання - Шулінова, Лариса Василівна (Київський національний університет імені Тараса Шевченка, 2014)
У статті розглянуто вербалізацію синестетичного світосприйняття в сучасному медійному тексті мистецької тематики як один із засобів реалізації функції впливу на реципієнта в інтернет-виданнях, зорієнтованих на широку аудиторію.

This article is devoted to synaesthesem’ world-view verbalization of modern media text relating to the study of art as a mean of realization of the function of influence on recipient in Internet-editions, directed towards wide audience. The special status of media texts relating to the study of art of modern mass media style is determined. The author analyzes mass media texts relating to the study of art, represented in the national nonspecialized editions, which enclosed particular headings about culture / art namely "Ukrainska pravda", "Den", "Ukraina moloda", "Tyzhden.ua".
Synesthesems in the Ukrainian mass media text about art: nonspecialized internet-editions
Keywords: синестезема; вербалізація; медійний текст; відчуття; почуття; synesthesem; verbalization; media text; sensation; feeling